Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Magnetic and dielectric properties and Raman spectroscopy of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Maity, Tuhin; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2010)
The rare earth orthochromites are extremely interesting due to the richness of their optical, dielectric, and magnetic properties as well as due to their multiferroic properties which make them suitable materials to study in the nanoregime. However, the wet-chemical synthesis of these materials in nanosize is nontrivial. Here, we report for the first time, the detailed Raman spectra as well as magnetic and dielectric properties of chemically synthesized GdCrO3 nanoparticles of size ranging from 40 to 60 nm. The magnetic properties are dictated by competing Cr3+-Cr3+, Gd3+-Cr3+, and Gd3+-Gd3+ superexchange interactions in different temperature regions, resulting into an antiferromagnetic ordering at 167 K due to the Cr3+-Cr3+ followed by weak ferromagnetic ordering due to the onset of Cr3+-Gd3+ interactions. At lower temperature, it shows weak antiferromagnetic ordering due to Gd3+-Gd3+ interaction. Below 95 K, GdCrO3 nanoparticles showed the presence of negative magnetization due to Gd3+ and Cr3+ interactions resulting into weak ferromagnetic coupling. The Raman spectroscopy shows the characteristic Raman shifts indicating that below 450 cm(-1), Gd3+ ions play a dominant role in determining the phonon frequencies of GdCrO3, and above 450 cm(-1), the Cr+3 ions dominate. We also present for the first time the low temperature dielectric constant and loss tangent data for GdCrO3 in a broad temperature and frequency range. The dielectric constant shows a decrease in comparison to the bulk values due to the size dependent effects. It also shows a peak centered at around 320 K above which it shows a sharp decrease. The dielectric loss value in GdCrO3 nanoparticles is quite small and shows an interesting frequency dependent anomaly at lower temperature which might be due to the coupling between magnetic and dielectric order parameters.
Keywords: dielectric losses; gadolinium compounds; Magnetisation; Multiferroics; nanofabrication; Nanoparticles; permittivity; phonons; Raman spectra; superexchange interactions

Study of hydration of sarcosine, formation of its zwitterion and their different oligomers in aqueous media: a Raman spectroscopic and theoretical study - Sharma, Poornima; Singh, Dheeraj K.; Gupta, Vineet; Asthana, B. P.; Mishra, P. C.; Singh, Ranjan K. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
{Raman spectra of the biologically important molecule sarcosine (SAR) (C3H7NO2) were studied experimentally in aqueous solution at different concentrations. These spectra were also calculated theoretically using density functional theory (DFT) at the B3LYP/6-31 1++G(d,p) level. Further, all the observed normal modes were assigned through potential energy distribution (PED). Geometry optimization of SAR produced its three conformers with slightly different energies. The lowest energy conformer of SAR was selected for a systematic solvation study wherein different numbers of water molecules (nW
Keywords: DFT calculations; Hydration; Oligomer; Raman spectra; Sarcosine; Zwitterion